Functional organization and visual representations of human ventral lateral prefrontal cortex - Chan, Annie W. (Frontiers in Psychology, 2013)
Recent neuroimaging studies in both human and non-human primates have identified face selective activation in the ventral lateral prefrontal cortex even in the absence of working memory demands. Further, research has suggested that this face-selective response is largely driven by the presence of the eyes. However, the nature and origin of visual category responses in the ventral lateral prefrontal cortex remain unclear. Further, in a broader sense, how do these findings relate to our current understandings of lateral prefrontal cortex? What do these findings tell us about the underlying function and organization principles of the ventral lateral prefrontal cortex? What is the future direction for investigating visual representations in this cortex? This review focuses on the function, topography, and circuitry of the ventral lateral prefrontal cortex to enhance our understanding of the evolution and development of this cortex.